2000
DOI: 10.3349/ymj.2000.41.2.185
|View full text |Cite
|
Sign up to set email alerts
|

The effective concentration and exposure time of mitomycin-C for the inhibition of lens epithelial cell proliferation in rabbit eyes

Abstract: The proliferation of residual lens epithelial cells following cataract surgery is assumed to be a major cause of posterior capsular opacification. To assess the efficacy of mitomycin-C in preventing posterior capsular opacification, we determined the effective concentration and exposure time of mitomycin-C in inhibiting rabbit lens epithelial cell proliferation. The fourth-passaged rabbit lens epithelial cells were maintained for one day and then exposed to mitomycin-C for 1, 2, 3, and 5 minutes, respectively.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2001
2001
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…The area of the wound was determined using NIH Image 1.6 (public domain image processing and analysis program for the Macintosh developed at the National Institutes of health and available on the Internet at rsb.info.nih.gov/nih-image/), and the percentage of wound healing was calculated by dividing the area of the wound at time X by the area of the wound at time 0 and multiplying by 100. In some experiments, to prevent cell proliferation, which could confound the analysis of cell migration into the wound, cells were preincubated with mitomycin C (10 g/ml) for 1 h at 37°C (50). To confirm that the observed reduction in keratinocyte migration induced by ISO was due to ␤ 2 -AR activation, in some experiments, human keratinocytes were preincubated for 15 min at 37°C in the presence or absence of timolol (20 M), a ␤ 2 -AR antagonist.…”
Section: Methodsmentioning
confidence: 99%
“…The area of the wound was determined using NIH Image 1.6 (public domain image processing and analysis program for the Macintosh developed at the National Institutes of health and available on the Internet at rsb.info.nih.gov/nih-image/), and the percentage of wound healing was calculated by dividing the area of the wound at time X by the area of the wound at time 0 and multiplying by 100. In some experiments, to prevent cell proliferation, which could confound the analysis of cell migration into the wound, cells were preincubated with mitomycin C (10 g/ml) for 1 h at 37°C (50). To confirm that the observed reduction in keratinocyte migration induced by ISO was due to ␤ 2 -AR activation, in some experiments, human keratinocytes were preincubated for 15 min at 37°C in the presence or absence of timolol (20 M), a ␤ 2 -AR antagonist.…”
Section: Methodsmentioning
confidence: 99%
“…[ 13 14 15 16 17 ] To date, only mechanical removal of the LECs by anterior lens capsule (ALC) polishing has been used clinically and other physical or pharmacological methods have not found application due to lack of sensitivity and specificity. [ 18 19 20 21 ] The ultrasound irrigation and aspiration tip was found to be the most effective instrument for mechanical polishing. [ 22 ]…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that the efficacy of MMC on the inhibition of rabbit lens epithelial cells in vitro is positively related in a dose-and time-dependent manner [18]. However, the characteristics of MMC-induced lens cell death and the mode of action of MMC on LEC death have not been studied in detail.…”
Section: Introductionmentioning
confidence: 96%
“…To determine cell viability, a 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyl tetrazolium bromide (MTT) assay was used [18]. ·-TN4 cells (5 !…”
Section: Determination Of Cell Viabilitymentioning
confidence: 99%